Reference range of fetal nasal bone length between 18 and 24 weeks of pregnancy in an unselected Brazilian population: experience from a single service. (August 2014) - Araujo Júnior, Edward; Martins, Wellington P.; Pires, Claudio Rodrigues; Moron, Antonio Fernandes; Zanforlin Filho, Sebastião Marques
Abstract Objective: To determine reference range of fetal nasal bone length (NBL) during the second trimester of pregnancy in a Brazilian population. Methods: This was a retrospective cross-sectional study with 2681 normal singleton pregnancies between 18 and 24 weeks of gestation. The NBL was obtained in the mid-sagittal plane of the fetal face profile using the following landmarks: nasal bone, overlying skin and the tip of the nose. The NBL was measured by placing the calipers in the out-to-out position. To assess the correlation between NBL and gestational age (GA), polynomial equations were calculated, with adjustments by coefficient of determination (R2). Results: The mean of NBL ranged from 5.72 ± 0.87 mm at 18–18 + 6 weeks to 7.45 ± 1.23 mm at 24–24+6 weeks of pregnancy. We observed a good correlation between NBL and GA, best represented by a linear equation: NBL = 0.080+0.276*GA (R2 = 0.16). Conclusion: We established a reference range of fetal NBL in the second trimester of pregnancy in a Brazilian population.